Continuous Hydrogenation of Ethyl Levulinate to 1, 4‐Pentanediol over 2.8Cu‐3.5Fe/SBA‐15 Catalyst at Low Loading: The Effect of Fe Doping. Issue 16 (17th July 2019) - Deng, Tianyu; Yan, Long; Li, Xinglong; Fu, Yao
Abstract: Bimetallic Cu–Fe catalysts with low loading were prepared for hydrogenation of ethyl levulinate (EL) to 1, 4‐pentanediol (1, 4‐PDO). Among them, 2.8Cu‐3.5Fe/SBA‐15 (Cu/Fe molar ratio of 1:1.5) performed best, capable of converting EL to the key intermediate γ‐valerolactone (GVL) at 140 °C with 97 % yield. It can also be used to hydrogenate GVL to 1, 4‐PDO with 92.6 % selectivity or convert EL to 1, 4‐PDO in one pot. The high activity of the catalyst at such a low loading was attributed to the highly dispersed metal species and the Fe doping effect. Various characterization methods indicated that Fe acted as both structural and electronic modifier to promote the chemical properties of the Cu species. Besides, the incorporation of Fe provided abundant Lewis acid sites and accelerated the reaction process. CuFeO2 was detected by energy‐dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and XRD. On the basis of a combination of characterization and reaction kinetics, synergistic catalysis by Cu 0 and CuFeO2 is considered to be responsible for the excellent performance of the Cu–Fe catalysts. Abstract : Iron is the dope : Cu–Fe/SBA‐15 bimetallic heterogeneous catalysts are prepared by the co‐impregnation method and used to flexibly convert biomass‐derived ethyl levulinate to high‐value γ‐valerolactone or 1, 4‐pentanediol. The promoting effect of the Fe dopant and the formed CuFeO2 phase are responsible for the high reactivity.